Analisa Green Accounting pada Aplikasi GaloninAja dalam Upaya Mewujudkan SDGs - Beni Suci Tapaningsih; Esmawati; Fatimah Azzahra (Jurusan Akuntansi Syariah Fakultas Ekonomi dan Bisnis Islam UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
Currently, Indonesia is the third largest producer of waste in the world. Plastic waste is the second largest waste produced after food waste, which is 15.1℅. Problems regarding plastic waste cannot be separated from human life, especially in terms of consumption of mineral water because a lot of the packaging uses plastic. Moreover, with the emergence of single-use gallons, the problem of plastic waste is increasing. In addition, as much as 46.21% of waste in Indonesia is not managed. If this is allowed to continue, it can cause environmental damage and even natural disasters such as floods, resulting in hunger and poverty. Viewed from the other side, the waste-producing company should be responsible for managing the waste by implementing green accounting. However, in Indonesia, not many companies have implemented green accounting. To solve this problem, the author makes an innovative GaloninAja application. GaloninAja is one of the technological innovations that can make it easy for users to transact and get benefits and will aggregately have an impact on reducing plastic waste that has the potential to pollute the environment. With this application, companies can implement green economics as one of the Sustainable Development Goals without having to lose costs for the environment (green accounting). This study uses a qualitative descriptive method with primary data sources in the form of interviews and secondary.